2021
DOI: 10.2147/cmar.s287993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognostic Factors of Salvage Stereotactic Body Radiotherapy for Post-Surgical Thoracic Oligo-Recurrence/Metastasis of Non-Small-Cell Lung Cancer

Abstract: Purpose The study aimed to assess the efficacy and safety of stereotactic body radiotherapy (SBRT) using CyberKnife (CK) in patients with postoperative thoracic oligo-recurrence/metastasis of non-small-cell lung cancer (NLCLC), and to analyze the prognostic factors affecting overall survival after SBRT. Patients and Methods A total of 44 patients with postoperative thoracic oligo-recurrence/metastatic of NLCLC treated with SBRT were reviewed. Thoracic oligo-recurrence/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Therefore, early diagnosis and treatment of NSCLC should be strengthened to reduce the possibility of postoperative recurrence. Some researchers studied the related factors of recurrence and metastasis in patients with NSCLC after minimally invasive resection and found that stages II and III were common independent risk factors for recurrence and metastasis in patients with NSCLC after minimally invasive resection, similar to the results of this study [ 13 ]. Lymph node metastasis was the most important mode of lung tumor metastasis, which meant tumor cell proliferation and growth in patients.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, early diagnosis and treatment of NSCLC should be strengthened to reduce the possibility of postoperative recurrence. Some researchers studied the related factors of recurrence and metastasis in patients with NSCLC after minimally invasive resection and found that stages II and III were common independent risk factors for recurrence and metastasis in patients with NSCLC after minimally invasive resection, similar to the results of this study [ 13 ]. Lymph node metastasis was the most important mode of lung tumor metastasis, which meant tumor cell proliferation and growth in patients.…”
Section: Resultssupporting
confidence: 87%
“… The synthetic pathway to generate naphthoquinone derivatives 9 – 16. Compounds 9 – 16 are synthesized from the corresponding aromatic amines and 2,3-dichloronaphthoquinone [ 1 , 4 , 19 , 20 , 21 ]. By using aryl urea in this reaction instead of an aromatic amine, we hoped to form an oxazole ring, but we failed to form 2-chloro-3-(phenylamino)-1,4-naphthoquinones 9 – 15 or 2-(4-hydroxyphenylamino)-1,4-naphthoquinone 16 .…”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…Cigarette smoking and exposure to various environmental pollutants results in rapidly rising cases of NSCLC worldwide [ 1 , 2 ]. Approximately 60–70% of all patients with NSCLC present with late and advanced stages of the disease involving multiple organ systems [ 2 , 3 , 4 ]. Patients with advanced-stage NSCLC are generally treated with aggressive surgery, chemotherapy, radiation, or a combination of these treatments [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations